Balanitis xerotica obliterans in non-identical (dizygotic) twin boys. - Nasr, B.; Shukla, R.; Corbett, H.J. (European Journal of Pediatric Dermatology, 2012)
Balanitis Xerotica Obliterans (BXO), also known as lichen sclerosus et atrophicus (LS), occurs in males of all ages; the underlying cause is unknown. There are few reports of familial BXO, although familial LS is well described in women and girls. We report almost synchronous presentation of BXO in non-identical twin boys.